China’s Economic Engagement in the Middle East - Dana M.D Sajadi; Waqar Ahmad (Cihan University-Erbil Journal of Humanities and Social Sciences)
The Middle East centers are approached by China and focus on promoting development as a means to address the region’s challenges. China’s geo-economics strategy for the broader Middle East primarily revolves around an external trade and industrial approach. This approach integrates geopolitical considerations with economic policies, effectively exporting industrial capacities. In essence, it functions as both a geo-industrial policy and a concurrent trade strategy. It offers a developmental model as a blueprint, prioritizes partnerships over alliances, and recognizes a crucial reality. Nonetheless, the instability of the US special program in the Middle East posed a fresh challenge to the future progress of bilateral relations. Importantly, China’s Middle East policy has not remained unchanged, its swift adaptations have injected energy into the positive growth of Sino-Arab bilateral relations. As China’s involvement in the Arab region and nearby areas grows, so does its influence on the global stage. This is what China seeks to achieve with all its capabilities and potential. The paper seeks to examine the role of China’s economic influence on the Middle East.